Rebuilding the Royal Navy warship design since 1945 - Brown, D.K. (David K.) (Naval Institute Press, 2003)
This fourth and final volume in the bestselling series on Royal Navy warship development presents an in-depth and lucid account of British warship construction in the challenging half-century since World War II. After considering the wartime legacy and lingering austerity, the authors cover some of the ambitious ideas for the bigger ships like the reconstruction of the carrier Victorious, and the conversion of fleet destroyers into anti-submarine frigates. But most of the book is devoted to new construction, with chapters on all the major categories and new information on designs that remained on the drawing board. It concludes with a survey of the most significant technological innovations and an analysis of the impact of the Falklands War. D. K. Brown's personal knowledge and experience and George Moore's in-depth research on declassified material add up to a crowning finale of an internationally acclaimed series. 200 plans and illustrations. 10 x 12 inches